Nilai-Nilai Moral dalam Novel Imperpect Karya Meira Anastasia - Ira Yuniati; Hasmi Suyuthi; Melisah Melisah (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
This study aims to describe the good and bad moral values ​​contained in the novel Imperpect by Meira Anastasia. This research was conducted using a structural approach because there is a relationship between the building elements, namely the intrinsic elements of the novel with moral values. Data analysis was carried out by classifying data, analyzing data, interpreting and drawing conclusions. The results of the study contained 49 data on moral values, consisting of 28 good morals and 17 bad moral values. The conclusion is that good morals in Meira Anastasia's novel Imperpect dominate more than bad moral values. Keywords: Good and Bad Moral Values, Novel, Structural Approach